2021
DOI: 10.1021/acs.jnatprod.0c01062
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic and Aliphatic Apiuronides from the Bark of Cinnamomum cassia

Abstract: Cinnamomum cassia Presl (Cinnamon) has been widely cultivated in the tropical or subtropical areas, such as Yunnan, Fujian, Guandong, and Hainan in China, as well as India, Vietnam, Thailand, and Malaysia. Four new glycosides bearing apiuronic acid (1, 4, 6, and 7) and their sodium or potassium salts (2, 3, and 5), together with 31 known compounds, were isolated from a hot water extract of the bark of C. cassia via repeated chromatography. The structures of the new compounds (1−7) were determined by NMR, IR, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Considering the large coupling values of H-7/8 ( 3 , J H‑7–H‑8 = 16.2 Hz; 4 , J H‑7–H‑8 = 15.9 Hz), their aglycones were trans -cinnamic acid and trans -cinnamic alcohol, respectively. A precise comparison of their 1D NMR data with those of 1 , 2 , and glycosides recorded in refs and and acid hydrolysis indicated that 3 and 4 had 6- O -(β- erythro - d -apiofuranosyl)-β- d -glucopyranosyl and 6- O -(β -erythro - d -apiofuranuronyl)-β- d -glucopyranosyl, respectively. As we know, d -glucuronic acid is generated via oxidation of d -glucose catalyzed by the key enzymes UDP-glucose dehydrogenase/ myo -inositol oxygenase. , Correspondingly, we also suggest that β -erythro - d -apiofuranuronyl in 4 is produced by the oxidation of β- erythro - d -apiofuranosyl catalyzed by potential dehydrogenase/oxygenase (apiofuranosyl in 1 – 3 was β- erythro - d -apiofuranosyl).…”
Section: Results and Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Considering the large coupling values of H-7/8 ( 3 , J H‑7–H‑8 = 16.2 Hz; 4 , J H‑7–H‑8 = 15.9 Hz), their aglycones were trans -cinnamic acid and trans -cinnamic alcohol, respectively. A precise comparison of their 1D NMR data with those of 1 , 2 , and glycosides recorded in refs and and acid hydrolysis indicated that 3 and 4 had 6- O -(β- erythro - d -apiofuranosyl)-β- d -glucopyranosyl and 6- O -(β -erythro - d -apiofuranuronyl)-β- d -glucopyranosyl, respectively. As we know, d -glucuronic acid is generated via oxidation of d -glucose catalyzed by the key enzymes UDP-glucose dehydrogenase/ myo -inositol oxygenase. , Correspondingly, we also suggest that β -erythro - d -apiofuranuronyl in 4 is produced by the oxidation of β- erythro - d -apiofuranosyl catalyzed by potential dehydrogenase/oxygenase (apiofuranosyl in 1 – 3 was β- erythro - d -apiofuranosyl).…”
Section: Results and Discussionmentioning
confidence: 88%
“…Six known relevant compounds, cryptamygin C ( 15 , CAS: 475632-39-4), methyl 2-[6- O -(β- erythro - d -apiofuranosyl)-β- d -glucopyranosyloxy]-dihydrocinnamate ( 16 , CAS: 1818196-70-1), cinnacassioside B ( 17 , CAS: 2763825-48-3), 7- O -β- d -glucopyranosyl-phenylmethanol ( 18 , CAS: 4304-12-5), (2 R *,3 R *)-5,7-dimethoxy-3′,4′-methylenedioxy-epicatechin ( 19 , CAS: 87562-72-9), and (2 R *,3 R *)-5,7,3′-trimethoxy-epicatechin ( 20 , CAS: 2518186-98-4) were identified by comparison of their spectroscopic data recorded in the literature.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Syringaresinol was obtained as previously described [ 36 ]. In brief, the dried Cinnamomum cassia bark (6.0 kg) was extracted with hot water (60 L, 100 °C) twice in water bath for 2 h and the solvent was vaporized at 45 °C in vacuo.…”
Section: Methodsmentioning
confidence: 99%
“…Syringaresinol directly affects microglia and macrophages to modulate the production of NO and related proteins, such as iNOS, and downregulates inflammatory signaling via the MAPKs pathway [ 22 , 33 , 34 , 35 ]. In our previous study, we investigated the analgesic effects of syringaresinol isolated from the bark of Cinnamomum cassia (Cinnamomi Cortex) on neuropathic pain induced by paclitaxel [ 36 ]. We also found that Cinnamomi Cortex has analgesic efficacy against OIPN [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has revealed that medicinal herbs have various pharmacological activities, such as antimicrobial, antioxidant, anti‐inflammatory, and anti‐nociceptive activities 19 . The potency of medicinal herbs is mediated by their bioactive compounds and phytochemicals 20–22 …”
Section: Introductionmentioning
confidence: 99%